2022
DOI: 10.3389/fmed.2022.980002
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of paxlovid in elderly patients infected with SARS-CoV-2 omicron variants: Results of a non-randomized clinical trial

Abstract: ObjectiveTo evaluate the efficacy of Paxlovid in treating Chinese elder patients infected with SARS-CoV-2 omicron variants.Materials and methodsWe performed a non-randomized, controlled trial in Shanghai, China. Participants infected with SARS-CoV-2 omicron variants were enrolled. All patients were divided into the Paxlovid group or the control group according to the Chinese guideline (version 9). The nucleic acid shedding time was the primary endpoint.ResultsAccording to the inclusion criteria, 142 patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…The differences in age distributions, related chronic diseases, vaccination rates, study designs, and SARS-CoV-2 variants may have contributed to the inconsistency between these studies. In a previous study related to the effect of paxlovid on the elderly patients with mean 76.37 years old who were infected with SARS-CoV-2 omicron variants, the nucleic acid shedding time was significantly reduced [ 25 ], which is consistent with the result of our research. Meanwhile we also found that the nucleic acid Ct value at admission was low in the elderly patients.…”
Section: Discussionsupporting
confidence: 92%
“…The differences in age distributions, related chronic diseases, vaccination rates, study designs, and SARS-CoV-2 variants may have contributed to the inconsistency between these studies. In a previous study related to the effect of paxlovid on the elderly patients with mean 76.37 years old who were infected with SARS-CoV-2 omicron variants, the nucleic acid shedding time was significantly reduced [ 25 ], which is consistent with the result of our research. Meanwhile we also found that the nucleic acid Ct value at admission was low in the elderly patients.…”
Section: Discussionsupporting
confidence: 92%
“…The pooled estimate of seven studies 15,16,19,21,26,31,33 involving 1187 patients showed a significant difference between the Paxlovid and no-Paxlovid groups in terms of PCR-negative conversion time (MD = −2.46; 95% CI: −4.31 to −0.61; p = 0.009) (Figure 2D).…”
Section: Pcr-negative Conversion Timementioning
confidence: 99%
“…In a double‐blind, placebo‐controlled phase II/III trial conducted by Pfizer Inc. Paxlovid™ has been found to reduce the hospitalization and death risk by 89% when administered within 3 days of symptom onset ( Table 4 ). Notably, the death rate was found to reduce with high statistical significance (p < 0.0001) [ 151 , 152 ]. A recent meta-analysis of 18,568 patient data from 41 RCTs comparing the efficacy of antiviral drugs in patients with COVID-19 found that malnupiravir and nimatrevir-ritonavir (Paxovid™) significantly reduced the risk of hospitalization and death.…”
Section: Variant Independent Therapiesmentioning
confidence: 99%